1986
DOI: 10.1038/323160a0
|View full text |Cite
|
Sign up to set email alerts
|

A physiological role for titin and nebulin in skeletal muscle

Abstract: Production of active force in skeletal muscle results from the interaction of myosin-containing thick filaments with actin-containing thin filaments. These muscles are also passively elastic, producing forces that resist stretch independently of ATP splitting or of interaction between the filaments. The mechanism of this passive elasticity is unknown; suggestions include gap filaments in the region between thick and thin filaments in muscles stretched beyond filament overlap, or intermediate filaments which co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
272
1
4

Year Published

1988
1988
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 420 publications
(293 citation statements)
references
References 27 publications
16
272
1
4
Order By: Relevance
“…The IDP have a number of characteristic properties: (1) aberrant molecular weight as determined by SDS gel electrophoresis [39] or gel permeation [39,40]; (2) high net charge at neutral pH and low content of hydrophobic amino acids [41]; (3) CD spectra that are similar to denatured or random coil proteins (minima near 200 nm and lack of minima in the 210-230 nm range typical of alpha helix and beta structure) [38]; (4) amino acid compositional bias with higher contents of lysineglutamic acid -proline and lower amounts of aromatic residues [42,43]; (5) absence of cooperative folding transitions when the protein is heated [39]; (6) sensitivity to proteolytic degradation [39]. Conditions (1), (2), (3), and (4) are clearly met by the polyE peptides E115 and E137 since they have elevated SDS gel apparent molecular mass (35 KDa vs 18 KDa actual and 15 KDa vs 8 KDa actual respectively, Table 2 and Fig. 1), high negative charge due to the preponderance of glutamic acid residues, CD spectra that fit the typical disordered pattern, and amino acid compositional bias.…”
Section: Titin Pevk and Intrinsic Protein Disordermentioning
confidence: 99%
See 1 more Smart Citation
“…The IDP have a number of characteristic properties: (1) aberrant molecular weight as determined by SDS gel electrophoresis [39] or gel permeation [39,40]; (2) high net charge at neutral pH and low content of hydrophobic amino acids [41]; (3) CD spectra that are similar to denatured or random coil proteins (minima near 200 nm and lack of minima in the 210-230 nm range typical of alpha helix and beta structure) [38]; (4) amino acid compositional bias with higher contents of lysineglutamic acid -proline and lower amounts of aromatic residues [42,43]; (5) absence of cooperative folding transitions when the protein is heated [39]; (6) sensitivity to proteolytic degradation [39]. Conditions (1), (2), (3), and (4) are clearly met by the polyE peptides E115 and E137 since they have elevated SDS gel apparent molecular mass (35 KDa vs 18 KDa actual and 15 KDa vs 8 KDa actual respectively, Table 2 and Fig. 1), high negative charge due to the preponderance of glutamic acid residues, CD spectra that fit the typical disordered pattern, and amino acid compositional bias.…”
Section: Titin Pevk and Intrinsic Protein Disordermentioning
confidence: 99%
“…It has multiple functions including sarcomere assembly, sarcomere stability maintenance [1], passive tension generation [2,3] and serine/threonine kinase activity [4,5]. The over 3 million Dalton molecular weight makes it the largest protein in nature.…”
Section: Introductionmentioning
confidence: 99%
“…Until recently it was believed to play a purely structural role in stabilising the myofilament lattice. However direct evidence from radiation inactivation experiments suggests that both nebulin and titin (another highmolecular-mass myofibrillar protein) are associated with the maintenance of resting tension within the muscle fibre [16]. Titin and nebulin can be phosphorylated, although only 15% of total titin phosphates exchanged with cytosolic ATP within 3 days; it has been suggested that the majority of phosphorylation sites are therefore more likely to have a structural, rather than a regulatory role [17].…”
Section: Discussionmentioning
confidence: 99%
“…Titin is a tandem array of Ig type C2 and fibronectin (FN) type III domains (Ï·300 per molecule) interspersed with unique sequences, most notably the Pro-, Glu-, Val-, and Lys-rich PEVK segment, and the N2A and N2B segments (5). The I-band segment of titin acts as a molecular spring, whose elastic properties define the passive or restoring mechanical properties of striated muscle (6)(7)(8)(9). By contrast, titin's A-band segment is thought to function as a scaffold that defines structural regularity within the A band (10).…”
mentioning
confidence: 99%